Effects of Aerobic Exercise as Add-On Treatment for Inpatients With Moderate to Severe Depression on Depression Severity, Sleep, Cognition, Psychological Well-Being, and Biomarkers: Study Protocol, Description of Study Population, and Manipulation Check - Imboden, Christian (Front Psychiatry, 2019)
Background: Aerobic exercise (AE) may be a non-pharmacological strategy to improve depression treatment and lessen the burden of somatic comorbidity of depression. Only few studies have examined the effect of AE as an add-on treatment for moderate to severe depression in an inpatient setting, and most studies have focused on depression severity and cardiovascular parameters. The purpose of the present article is to present the study protocol, to provide information about the assessed study population, and to perform a manipulation check in order to examine whether the intervention program was properly implemented. Methods: We conducted a randomized controlled trial in two centers comparing 6 weeks of AE to a placebo control intervention (stretching) as an add-on to standardized inpatient treatment of moderate to severe depression. Besides depression severity, several other psychological and biological variables were measured such as salivary cortisol, brain-derived neurotropic factor, cognitive tests, and polysomnography. To evaluate long-term effects of the intervention, we also scheduled a follow-up 6 months after completion of the study intervention. Results: Forty-five patients were randomized to either AE (n = 23) or the placebo intervention (n = 22); 36 patients completed the 6-week intervention. In the AE group, 65% completed all 18 training sessions. Patients who were less physically active prior to admission were less likely to complete the study. With regard to energy expenditure, mean kcal/kg/week was 16.4 kcal/kg/week (range: 13.8–17.7), coming close to the targeted dose of 17.5 kcal/kg/week. Conclusions: Overall, patients showed good adherence to the intervention protocol despite at least moderate depression severity. However, the dropout rate suggests that depressed inpatients may need special support to adhere to a structured exercise intervention program. This study will add evidence on the effects of AE as an add-on to inpatient treatment of moderate to severe depression. Besides antidepressant effects, potentially beneficial effects of AE on a broad array of further variables associated with depression will be evaluated. Clinical Trial Registration: www.ClinicalTrials.gov, identifier NCT02679053.